Impacts of Regional Speed Control Strategy Based on Macroscopic Fundamental Diagram on Energy Consumption and Traffic Emissions: A Case Study of Beijing - Wang, Wensi; Wang, Zirui; Wang, Guangjun; Yu, Bin; Xu, Yuhe; Yu, Kun (Frontiers in Public Health, 2022)
Numerous studies shown that particulate matter in the ambient environment has a significant impact on the health of the respiratory system. To understand the interrelationships between urban built environment, transportation operations and health, this study proposes an innovative approach that uses real-world datasets to assess the health impacts of energy consumption and emissions from transportation operations in both spatial and temporal dimensions. In the specific case of Beijing, the GPS data of the traffic network in the Fourth Ring Road was processed, and the obtained data allowed to test the impact of traffic control strategies during peak hours on energy consumption and emissions. Changes in PM2.5 concentrations around four different built-up areas were calculated and compared. The results of this paper show that the PM2.5 concentration generated by the main road in the urban built roads can be 2 to 4 times that of the general road, and the PM2.5 concentration emitted by the traffic on the ring road (main road) during peak hours can reach up to 250 μg/m^3, while the traffic emission concentration on ordinary roads near residential areas is only 50 μg/m^3. Adopting velocity control strategie on key roads can effectively reduce vehicle energy consumption by 40% and PM2.5 emissions by 76%. For the health of travelers (such as roadside jogging behavior), the PM2.5 inhalation of night running in commercial and entertainment areas is about 1.3-2.6 times that of night running in residential areas. Compared with morning or night runners, commuters had a corresponding 10.3% higher risk of developing respiratory problems. The research results provide a useful reference for energy conservation and emission reduction control strategies for different road types in cities and help existing cities to establish a traveler health evaluation system caused by traffic operation.